Enhancing the performance of double-flush riveted joints through hybridization with adhesive bonding - João M.B. Alpendre; Pedro M.S. Rosado; Rui F.V. Sampaio; João P.M. Pragana; Ivo M.F. Bragança; Carlos M.A. Silva; Paulo A.F. Martins (Journal of Advanced Joining Processes)
This paper explores the potential to enhance the mechanical performance of joints created through a new joining-by-forming technique called hybrid double-flush riveting. To achieve this, adhesive bonding is used to form hybrid lap joints with superior mechanical properties. The study focuses on high-strength steel sheets and starts by identifying the appropriate surface conditions necessary for producing strong adhesive-bonded joints. A similar strategy is applied to construct double-flush riveted joints, focusing on the geometric variables involved in the process. Hybrid joints are then created by integrating adhesive bonding with double-flush riveting, with the second carried out before or after curing is completed. The experimental development is supported by finite element analysis conducted with an in-house computer program.The mechanical performance of the hybrid joints is compared to that of purely adhesive-bonded and conventionally double-flush riveted joints through shear and peel destructive testing. Results demonstrate that hybrid joints ultimately provide greater joint strength for both solicitations. This allows showcasing the hybridization of double-flush riveting with adhesive bonding as an effective solution for applications where joint strength and continuity are essential.